Comment le témoignage devient une œuvre littéraire : Le cas de Robert Antelme et de Primo Levi - Teklik, Joanna (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2006)
Can a testimony, a text similar to a document, be a literary work? The answer to this question is definitely positive in the case of R. Antelme (L'espèce humaine) and P. Levi (Se questo è un uomo) who relate their experience from a concentration camp. These authors, remaining faithful to the truth, do not neglect aesthetic requirements, using known narrative techniques and skillfully maintaining the tension characteristic of literary texts. They use an innovative form of narration. It is fragmentary and broken, which fully reflects the character of the prisoners' fate. Finally, a new conception of humanity and a deep reflection on human nature (the titles are meaningful themselves) prove the literary character of both texts.
How testimony becomes a literary work: the case of Robert Antelme and Primo Levi